Immune checkpoints and their inhibition in cancer and infectious diseases. Issue 5 (24th April 2017) - Dyck, Lydia; Mills, Kingston H.G.
Abstract : T cells are activated by dendritic cells, leading to effector T‐cell differentiation. Chronic exposure to tumors or pathogens can enhance expression of immune checkpoints and induce a suppressed, regulatory, or anergic T‐cell phenotype. This can be prevented or reverted by immune checkpoint blockade, thus unleashing effector T‐cell responses. Abstract : The development of chronic infections and cancer is facilitated by a variety of immune subversion mechanisms, such as the production of anti‐inflammatory cytokines, induction of regulatory T (Treg) cells, and expression of immune checkpoint molecules, including CTLA‐4 and PD‐1. CTLA‐4, expressed on T cells, interacts with CD80/CD86, thereby limiting T‐cell activation and leading to anergy. PD‐1 is predominantly expressed on T cells and its interaction with PD‐L1 and PD‐L2 expressed on antigen‐presenting cells (APCs) and tumors sends a negative signal to T cells, which can lead to T‐cell exhaustion. Given their role in suppressing effector T‐cell responses, immune checkpoints are being targeted for the treatment of cancer. Indeed, antibodies binding to CTLA‐4, PD‐1, or PD‐L1 have shown remarkable efficacy, especially in combination therapies, for a number of cancers and have been licensed for the treatment of melanoma, nonsmall cell lung cancer, and renal and bladder cancers. Moreover, immune checkpoint inhibitors have been shown to enhance ex vivo effector T‐cell responses from patients with chronic viral, bacterial, or parasitic infection, including HIV, tuberculosis, and malaria. Although the data from clinical trials in infectious diseases are still sparse, these inhibitors have great potential for treating chronic infections, especially when combined with therapeutic vaccines.